2004
DOI: 10.1021/bi049000s
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Loops in the Structure of Lactose Permease

Abstract: Structural analysis of peptide fragments has provided useful information on the secondary structure of integral membrane proteins built from a helical bundle (up to seven transmembrane segments). Comparison of those results to recent X-ray crystallographic results showed agreement between the structures of the fragments and the structures of the intact proteins. Lactose permease of Escherichia coli (lac Y) offers an opportunity to test that hypothesis on a substantially larger integral membrane protein. Lac Y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…A large body of literature supports the basic assumption of the model: For example, proteolysis of membrane proteins resulted in fragments containing entire TM sequences (Huang et al 1981), and chemically or recombinantly synthesized TM peptides spontaneously assembled thereby rescuing receptor activity (Kahn and Engelman 1992;Ridge et al 1995;Martin et al 1999;Wrubel et al 1994). Finally, peptides corresponding to the N and C terminus (Harmar 2001;O'Hara et al 1993), loop domains (Bennett et al 2004;Katragadda et al 2001a, b;Yeagle et al 2000) and transmembrane domains (Katragadda et al 2001a, b;Cohen et al 2008;Zheng et al 2006;Musial-Siwek et al 2008;Tian et al 2007;Lau et al 2008;Mobley et al 2007;Neumoin et al 2007) from GPCRs have been found to fold to distinct secondary structures which in certain cases resembled the structures of the corresponding regions of the intact receptor.…”
Section: Introductionmentioning
confidence: 96%
“…A large body of literature supports the basic assumption of the model: For example, proteolysis of membrane proteins resulted in fragments containing entire TM sequences (Huang et al 1981), and chemically or recombinantly synthesized TM peptides spontaneously assembled thereby rescuing receptor activity (Kahn and Engelman 1992;Ridge et al 1995;Martin et al 1999;Wrubel et al 1994). Finally, peptides corresponding to the N and C terminus (Harmar 2001;O'Hara et al 1993), loop domains (Bennett et al 2004;Katragadda et al 2001a, b;Yeagle et al 2000) and transmembrane domains (Katragadda et al 2001a, b;Cohen et al 2008;Zheng et al 2006;Musial-Siwek et al 2008;Tian et al 2007;Lau et al 2008;Mobley et al 2007;Neumoin et al 2007) from GPCRs have been found to fold to distinct secondary structures which in certain cases resembled the structures of the corresponding regions of the intact receptor.…”
Section: Introductionmentioning
confidence: 96%
“…An understanding of how these factors affect ion channel function requires an understanding of how the transmembrane helices fold together to form a fully functional channel. The feasibility of a reductionist approach to understanding nAChR structure has been established by the crystal structure of the isolated EC domain of the mouse α1 nAChR subunit [15], and by comparing the crystal structures of other membrane proteins to NMR analyses of isolated domains [35, 36]. …”
Section: Introductionmentioning
confidence: 99%
“…The contribution of loop domains to the overall structural stability, function and folding has been recognized for some membrane proteins. [11][12][13][14] To gain insights into the contributions of the extra-membranous domains to folding and stability of membrane proteins we have designed model peptides incorporating folding domains that span the membrane and extend into the aqueous phase. 15,16 As a model for this study, we have used MS1, a peptide system previously developed to elucidate the features influencing transmembrane helix association.…”
Section: Introductionmentioning
confidence: 99%